HUBUNGAN ANTARA DERAJAT KEPARAHAN AKNE VULGARIS DENGAN TINGKAT STRES PADA REMAJA DI POLI KULIT RSUD PROF.Dr SOEKANDAR MOJOSARI - Virda Yuniarti, Enny (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Acne vulgaris or acne is one of skin problems that most confusing for the young, marked by popul, nodul, pustule, comedo can tube scar couse confident crisis phsycosocial effect just like stress. The purpose of this research is to know the relation ship between the gradation acne vulgaris by level stress of the young in skin unit RSUD Prof. Dr. Soekandar Mojosari. Analitic correlation research design with cross sectional approach. The patients who comes to skin caos unit are young teenages with diagnose acne vulgaris, and with the accidental sampling technic sample get 20 young sample. The method of the collecting data uses questioner and observation by using check list instrument on September to October 2014. The data finally is analsyed by using prosentase and cross tabulation as the result, founded 60% acne vulgaris moderate tipe and 65% stres level normal. The conclusion is there is not relation between gradation acne vulgaris by level stress of the young, because most of acne vulgaris triggered by physiologis disorder of the body. Acne vulgaris can not tigger stress level of moderate or severe. Young is hoped can improve their knowledge about the prevention and handling of acne vulgaris stress, so it can improve their quality in a future.Key words: acne vulgaris, young or teenage, stress levels.